ASSESSING ENTERPRISE STABILITY THROUGH FINANCIAL ANALYSIS (International journal of artificial intelligence, 2026)
This article examines the assessment of enterprise stability through financial analysis tools. In the context of a market economy, ensuring long-term sustainability, competitiveness, and financial security of enterprises is considered a key priority. The study analyzes the essence and significance of core financial indicators used to evaluate the financial condition of enterprises, including liquidity, solvency, financial independence, and profitability, as well as their interrelationships. Furthermore, based on the results of financial analysis, internal and external factors influencing enterprise stability are identified, and scientific and practical conclusions aimed at improving financial management efficiency are proposed. The findings of the study are of practical relevance for enterprise managers, financial analysts, and specialists engaged in economic and financial analysis.